Physicians’ inclination towards standard guidelines and regulations on incentive based prescribing practices in Karachi. A mixed methods study design. - Mishal Sameer Khan; Afifah Rahman Shepherd; Zahida Azizullah; Sabeen Shareef Khan; Muhammad Naveed Noor; Nina van der Mark; Sadia Shakoor; Rumina Hasan; Amna Rehana Siddiqui (Journal of the Pakistan Medical Association)
Objective: To investigate private General Practitioners’ (GPs) interest in continuous professional development (CPD), with a focus on ethical practices. Methods: A mixed method study design conducted a cross-sectional survey of registered private GPs (n=419) in Karachi was conducted in the year 2022 on their professional and ethical practices with perspectives on engagement in training in the year 2022. Qualitative interviews were conducted with 28 GPs to get a deeper understanding of their views on professional development. Results: The median age of participants was 55 years (IQR 48-63 years) and 361 (86.2%) were males. The median number of years of professional experience was 31.0 years (IQR 24-37 years). It was observed that 116 (27.6%) of GPs saw more than 50 patients per day, and 377 (90%) met with pharmaceutical sales representative (PSR) regularly. Reported awareness of guidelines on ethical practices was 325 (77.6.0%), and willingness to sign a pledge committing to a code of ethics and to be part of a professional network of ethical doctors was high, 389 (~93.0%). However, both qualitative and quantitative data indicated that GPs had limited time for training, despite the interest in filling gaps in knowledge about ethical practice. Conclusion: Most GPs were willing to engage in CPD activities with a focus on ethics. Many GPs met regularly with PSRs, and CPD may reduce the pharmaceutical industry influence on their prescribing practices. Keywords: General Practitioner, Ethical practices, Mixed methods